De estudante a professor: a formação do futuro professor de matemática no contexto do estágio supervisionado - Scalabrin, Thanize Bortolini (2018)
The present research was developed in the Graduate Program in Mathematics Education and Teaching of Physics, Master's level, at the Federal University of Santa Maria (UFSM), and is inserted in the context of Supervised Curricular Internship, with the main objective of investigating how the UFSM licensing teacher in Mathematics becomes a teacher in the diverse actions of the Internship. As an initial introduction to the subject, it was verified, from the mapping of theses and dissertations cataloged in the period from 2001 to 2012, a concentration of 20 investigations that dealt with Supervised Curricular Internship in the formation of the Mathematics teacher of the final years of Elementary School and from high school. In addition, researching the course of constitution of the degree course in Mathematics of UFSM, it was identified that the course is in the process of curricular reformulation in order to comply with Resolution no. 2, of July 1, 2015. Also, to guide studies in education as development and humanization presuppositions, the Historical-Cultural Theory and, more specifically, Activity Theory were listed as the main theoretical references. The data were produced from the monitoring of the subject of Supervised Mathematics in Elementary School at UFSM, and were managed from the researcher's field diary records, audio recordings, reports developed by the students and a reflective session. In organizing these instruments, four units of analysis emerged: on the school and its organization; on teaching; about becoming a teacher and about the Internship. In relation to the school and its organization it was possible to identify that the trainees' attention was drawn to the norms; the physical structure; parental involvement; the commitment to the students and, above all, the way in which they received them. When observing the teaching of the regent teacher, they appropriated some ways of organizing the teaching, identifying: the changes of the students' behavior in relation to the methodologies adopted by the teacher; the teacher-student approach; silence is no guarantee of learning; the relevance of talking with students before starting the class and ways to keep students alert. By placing himself in the movement of becoming a teacher and seeing himself in the situation of ruling a class, the trainees realized the relevance of knowing the student; overcome insecurity; to motivate students; to seek differentiated methodologies; to look for modes of class domain; to be concerned with learning; to seek help from peers; to share experiences. Finally, when instigated to speak of the contributions of the Internship for their formation, future teachers expressed the significance of understanding the student; learn about planning; understand that what is easy for them may not be for students; know that the teacher has experiences outside of school; show that it is possible to dream; and that being a teacher is more than teaching. Thus, the four units allowed us to understand the phenomenon of Supervised Internship in Mathematics in Elementary School in the Mathematics Degree course of UFSM.